Decisions to use antibiotics for upper respiratory tract infections across China: a large-scale cross-sectional survey among university students - Stephan Harbarth; Chunling Lu (BMJ Open)
Objectives To investigate the decision-making process of Chinese university students with respect to antibiotic use for upper respiratory tract infections (URTIs).Design A cross-sectional questionnaire study.Setting The participants recruited from six universities across all Chinese regions from September to November 2015.Participants A total of 2834 university students sampled across six Chinese regions who self-reported experiencing symptoms of URTI within the past month completed the survey.Outcome measures The prevalence of decisions for treatment and antibiotic use for URTIs as well as knowledge about antibiotic use were measured by a self-administrated questionnaire. Using regular and multinomial logistic regression a nd adapted health belief model, we identified and measured a number of variables as potential risk factors for antibiotic misuse behaviours in order to explain and predict people’s treatment decisions and antibiotic use including knowledge, perceptions, access to antibiotics and cues to action.Results Of the 2834 university students who self-diagnosed a URTI, 947 (33.4%) self-reported having taken antibiotics; among them, 462 (48.8%) used non-prescription antibiotics, which came principally from left-over prescriptions (29.0%) and over-the-counter purchases at retail pharmacies (67.3%). One in four who sought care pressured their doctors for antibiotics; all received them. Those who perceived greater severity of the disease, had access to antibiotics, perceived benefits of using antibiotics (for the common cold: adjusted OR (aOR)=2.55, 95% CI 1.93 to 3.38 or as anti-inflammatory drugs: aOR=1.35, 95% CI 1.12 to 1.63), and were cued to action (eg, seeing presence of fever: aOR=2.05, 95% CI 1.62 to 2.60 or self-diagnosing their current infection as severe: aOR=1.86, 95% CI 1.41 to 2.45), keeping antibiotics at home (aOR=2.27, 95% CI 1.83 to 2.81) and access to over-the-counter antibiotics (aOR=2.00, 95% CI 1.63 to 2.45), were more likely to misuse antibiotics.Conclusions Misconceptions of antibiotic efficacy and easy access to antibiotics—with or without a prescription—were associated with antibiotic misuse among Chinese university students, which calls for context-appropriate multifaceted interventions in order to effectively reduce antibiotic misuse.